PEMBERDAYAAN MASYARAKAT DI DESA SOKO KABUPATEN PURWOREJO BERBASIS AIR BERSIH, DRAINASE, DAN LIMBAH DOMESTIK - Harsoyo harsoyo; Ilya Fajar Maharika; widodo brontowiyono (UII, 2016)
Soko village is a village located 8 km south of the town of Purworejo and in the District Bagelen. Geographically, the village of Soko is a hilly region that consists of 5 Hamlet is Krajan, Mojosongo, Sukolegok, Kebonkuning 1 and Kebonkuning 2.Permasalahan difficulty of clean water when dry and rainy seasons causing these areas clean water crisis. During the dry season the water receded and no resources at all. And when the rainy season the water became dirty due to poor drainage and yard waste from residents who go to the source of clean water.The purpose of the implementation of KKN PPM in the village Soko Bagelen districts are: 1) The creation of a favorable environment infrastructure (water, drainage, and sewage), 2) availability of clean water for 4 hamlets, and the creation of alternative water sources through self mapping.The target to be achieved is the creation of the role of NGOs would be willing to clean water for four hamlets (160kk), the creation of environmentally sustainable infrastructure, 3) The creation of an alternative water source.While the methods to be used in achieving that goal is to provide guidance to communities, training, and implimentasi. This activity is supported by the Agency for Family Planning and Community empowerment purworejo district.